Analysis of photo-excited thin superconducting films for optoelectronic device applications. - Majedi, A.H (IEEE Transactions on applied superconductivity)
This paper introduces a steady state photoresponse analysis in superconducting thin films. A model is developed for investigating the capability of superconductors for potential optoelectronic applications. First, we consider the thermodynamical variation under the application of continuous optical radiation in superconducting state. Then, the photo-induced changes in electrical parameters are evaluated from thermodynamical variations using the electrodynamics based on the BCS theory. All variations are considered as a function of optical characteristics along with the material properties. The numerical simulation gives us the optimum range of applied optical frequency and absorbed radiation intensity required for sensitive control of superconducting properties for optoelectronic and microwave applications.